Exports, Domestic Demand, and Economic Growth in China: Granger Causality Analysis - Wong Hock Tse (2010)
This study examines Granger causality among exports, domestic demand, and economic growth in China using time‐series data over the period from 1978 to 2002. This study uses three measures for domestic demand, namely household consumption, government consumption, and investment. The results show bidirectional Granger causality among these variables, namely exports, domestic demand, and economic growth. Thus, there is a dynamic relationship among exports, domestic demand, and economic growth. Exports and domestic demand are both important for economic growth in China. Moreover, economic growth in China has an impact on its exports and domestic demand. A successful and sustained economic growth requires growth in both exports and domestic demand.